Georgia : Third Review Under the Stand-By Arrangement and Requests for Augmentation, Extension of the Arrangement, Rephasing of Purchases, and Modification of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Third Review under the Stand-By Arrangement for Georgia. With monetary policy impaired by high dollarization, the authorities' response to the downturn relies mostly on fiscal stimulus. The reduction of policy interest rates and ample liquidity injections have not led to a resumption of bank lending, owing to balance sheet weaknesses and higher credit risk. The authorities have thus decided to accommodate tax revenue losses in a higher deficit in 2009. The authorities have requested an augmentation of access and an extension of the arrangement through mid-2011.